Exploring Additive Manufacturing Technologies in Engineering: A Comprehensive Study - Amit Rakshit (International Journal of Machine Systems and Manufacturing Technology, 2024)
The objective of this research was to systematically elucidate various pathways in casting, focusing on the utilization of Additive Manufacturing (AM) technology and its transformative impact on investment casting. The purpose of this systematic review is to ascertain whether AM may be a practical solution for investment casting production. Diverse databases, including Google Scholar, Research Gate, Mendeley, and Science Direct, were utilized for comprehensive research. When compared to creative techniques like employing additive manufacturing to create wax patterns for low-volume production, traditional investment casting techniques may prove to be less effective in terms of cost and turnaround time. Addressing this challenge, additive manufacturing has been introduced for pattern creation in investment casting processes. The paper critically examines the specific applications of rapid prototyping within the casting industry. After applying the inclusion criteria this study concluded that using Additive manufacturing in investment casting in place of the unadventurous method is more cost-effective and time-efficient.
Keywords: 2d cross-sections; Additive manufacturing; Rapid Prototyping; rapid investment casting; sintering